2019
DOI: 10.2209/tdcpublication.2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Dental Plaque Scores in Long-term Care Facilities Using a Checklist and Random Inspections: A Pilot Study

Abstract: The development and use of tailored interventions in overcoming barriers to optimum health in long-term care facility residents is of the highest importance. One successful approach to improving health outcomes is the use of a checklist by health care providers. Despite the evidence of the success of such checklists in nursing and medicine, there is little evidence on their use in improving dental outcomes. This study investigated whether an intervention comprising the daily use of a checklist for oral care by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Control group: those who did not practice tooth brushing 6 mos Dental nurses Improved oral health perception, lower plaque & gingival & inflammation scores & less clinical attachment loss Leon et al (2019) [ 91 ] Application of 5000 ppm NaF-dentifrice. Control group: 1450 ppm NaF-dentifrice 24 mos N/A 5000 ppm F-dentifrice more effective than conventional dentifrice in preventing & arresting RCLs Laurence et al (2019) [ 92 ] Educational sessions for nursing staff. Control group: those not receiving intervention 2 mos Dentist Improved plaque scores Saleem et al (2019) [ 93 ] Provided lip trainer device to one group, sonic toothbrush to other group & others as control 6 mos Clinician Dental hygienist Lip training device improved salivary flow rates & oral wettability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control group: those who did not practice tooth brushing 6 mos Dental nurses Improved oral health perception, lower plaque & gingival & inflammation scores & less clinical attachment loss Leon et al (2019) [ 91 ] Application of 5000 ppm NaF-dentifrice. Control group: 1450 ppm NaF-dentifrice 24 mos N/A 5000 ppm F-dentifrice more effective than conventional dentifrice in preventing & arresting RCLs Laurence et al (2019) [ 92 ] Educational sessions for nursing staff. Control group: those not receiving intervention 2 mos Dentist Improved plaque scores Saleem et al (2019) [ 93 ] Provided lip trainer device to one group, sonic toothbrush to other group & others as control 6 mos Clinician Dental hygienist Lip training device improved salivary flow rates & oral wettability.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies focused on interventions for the caretakers of older residents that included educational sessions and demonstrations on oral hygiene and denture care [ 92 , 98 ]. Such intervention reduced the plaque and gingival indexes in the older residents and improved knowledge and attitudes on oral health among their caretakers.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers 13,[28][29][30] have indicated that individually tailored interventions, such as the one employed by the Empower model of care, can improve oral hygiene outcomes resulting in reduced plaque levels. These results indicate that after attending four education sessions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…12 There is broad evidence that oral health can be maintained successfully with effective oral selfcare. 5,13,14 Additionally, research shows varying degrees of success with oral hygiene programs among partial denture wearers. 15,16 However, it has also been reported that the methods of oral hygiene instruction are not as significant as the need for oral hygiene instruction to be followed up and repeated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation